2001
DOI: 10.1007/bf02492487
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography method development and optimization by statistical experimental design and chromatogram simulations

Abstract: SummaryA liquid chromatographic method has been optimized by the use of an experimental design and chromatogram simulations. The strategy applied started with a statistical experimental design in which so-called beta coefficients were extracted from the mathematical model. Optimization was then performed by simulating the chromatographic separation with computer software.The effects of the variables (factors) are visualized in a way that is familiar to the analytical chemist. Simulation of chromatograms from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In another work [80] a liquid chromatography method was optimized based on an experimental design and chromatogram simulations and applying an experimental design. Results from the optimization of an LC method, including the separation of six peaks within 11 min were presented.…”
Section: Computer-assisted Optimization Of Se-parationsmentioning
confidence: 99%
“…In another work [80] a liquid chromatography method was optimized based on an experimental design and chromatogram simulations and applying an experimental design. Results from the optimization of an LC method, including the separation of six peaks within 11 min were presented.…”
Section: Computer-assisted Optimization Of Se-parationsmentioning
confidence: 99%
“…The desirability values generally in the range of 0-1. If the value is near to zero means the solution of the method is not strong whereas the value toward 1 means the solution or method is very strong [44]. The obtained desirability value was found to be; D=0.899 which indicated that the method is effective.…”
Section: Optimization Of Hplc Methods By Doementioning
confidence: 93%
“…The polynomial equation in terms of the actual components and factors was shown in Table 2. A positive value represents an effect that favors optimization and negative value shows an inverse relationship between the factor and response [44,47]. Table 2 illustrated that A, C, BC and C 2 were significant (<0.0001) model term for Rt of LAM.…”
Section: Optimization Of Hplc Methods By Doementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental design and information data analysis detects the factors that are significant and whether there are any interaction influences between the factors. Experimental statistical design has several uses in chemistry, e.g., in synthesis, separation, optimization of logical approaches (Harang et al, 2001;Rautio et al, 2009;Singireddy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%